Detection of Neoehrlichia mikurensis in 11 persons who attribute their persistent health complaints to a tick-borne disease - Audun Olav Dahlberg; Audun Aase; Harald Reiso; Rune Midgard; Hanne Quarsten (Ticks and Tick-Borne Diseases)
Background: Neoehrlichia mikurensis infections can cause symptomatic disease, particular among immunosuppressed persons. Long-lasting asymptomatic carriage of N. mikurensis may be common in endemic areas. This study explores possible associations between carriage of N. mikurensis DNA and persistent health complaints in persons who attribute their symptoms to a tick-borne disease. Methods: Eleven persons tested positive for N. mikurensis DNA by PCR in a study cohort of 285 persons reporting persistent health complaints. The 11 persons were tested again in a follow-up sample. Oral doxycycline treatment was given if the confirmatory PCR-test was positive. Treatment response was assessed by telephone interview. Demographics, clinical manifestations, tick exposure, physical health, somatic symptom burden and fatigue were compared to persons with negative N. mikurensis PCR (controls, N = 274). Results: Six persons had detectable N. mikurensis DNA in a follow-up sample up to 9.5 months after the index sample. Seven persons (one without a positive confirmative test) received doxycycline treatment. Three reported symptom restitution after completed antibiotic treatment. However, their symptoms were not clearly attributed to infection by N. mikurensis. We did not find any significant differences between infected persons and non-infected controls regarding their clinical manifestations and health burdens. Conclusions: We corroborate previous evidence of long-term carriage of N. mikurensis, but cannot infer that to be causative of persistent health complaints.